Theological Study of the Hanikit Tradition in the Atoen Pah Meto Bi Pah Soe Culture - South Central Timor, East Nusa Tenggara - Selan, Yunus; Putra, Adi; Harti, Sri Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Hanikit tradition significantly influences the social, cultural, and religious life of the Atone Pah Meto community in South Central Timor, East Nusa Tenggara. Through rituals like Futus, it serves as an expression of gratitude to God and a key part of the local cultural identity. This study explores the theological aspects of the Hanikit tradition, focusing on its alignment with biblical teachings. Using a qualitative approach, data were collected through observations, interviews, and documentation. The findings reveal that while the tradition reflects biblical values, such as reverence for God, certain elements of the Futus ritual require critical review to align with Christian faith. The study concludes that the Hanikit tradition can be contextualized within the Christian framework by removing incompatible elements, preserving its role as a cultural expression that strengthens faith.